Роль государственного регулирования в обеспечении развития национальной инновационной системы - Исаншина, Г. Ю. (НТУ "ХПИ", 2010)
Розглянуто основні методи і інструменти державного регулювання інноваційної діяльності. Досліджено чинники, які впливають на впровадження інновацій на підприємствах. Визначено систему податкових пільг, які забезпечать підтримкою підприємства на всіх етапах реалізації інноваційних проектів. Сформовано основні напрями побудови ефективної національної інноваційної системи.

The basic methods and tools of state regulation of innovative activity are considered. The factors interfering introduction of innovations at the enterprises are investigated. The system of tax privileges which will provide support of the enterprises at all stages of realisation of innovative projects is defined. The basic directions of construction of effective national innovative system are formulated.
Keywords: инновационная деятельность; налоговые льготы; венчурный капитал; инновационные проекты; источники финансирования; защита прав собственности